Aktivitas Antioksidan, Kadar Flavonoid, dan Fenolik Total Cangkang Kerang Mutiara (Pinctada maxima): Antioxidant Activity, Flavonoid Content, and Total Phenolics of Pearl (Pinctada maxima) Clam Shells - Ngibad, Khoirul; Muadifah, Afidatul; Sukmawati, Datin An Nisa (KOVALEN: Jurnal Riset Kimia, 2023)
Antioxidant compounds are able to dampen or ward off free radicals. Living things including pearl mussels (Pinctada maxima) can produce secondary metabolite compounds (phenolics, alkaloids, and terpenoids). There have been no studies on the antioxidant potential, flavonoid content, and total phenolics of pearl clam shells. This study aimed to determine the antioxidant potential of pearl clam shell ethanol extract (EECKM) in vitro using the DPPH method. In addition, it aims to determine the total flavonoid and phenolic levels of EECKM. The powder of pearl mussel shells is soaked with ethanol and the filtrate is concentrated until a concentrated extract is obtained. Flavonoid and phenolic levels from EECKM were measured using a UV-Vis spectrophotometer. Measurement of antioxidant activity using the DPPH method. EECKM has a yield of 1.73%, flavonoid levels of 0 mg QE/g, and total phenolics of 4.8 mg GAE/g. The extract has the highest antioxidant activity for a concentration of 100 mg / L with a percent value of DPPH radical inhibition of 67.1%.